2023
DOI: 10.5853/jos.2023.00185
|View full text |Cite
|
Sign up to set email alerts
|

Borderzone Infarcts and Recurrent Cerebrovascular Events in Symptomatic Intracranial Arterial Stenosis: A Systematic Review and Meta-Analysis

Abstract: Background and Purpose Intracranial arterial stenosis (ICAS)-related stroke occurs due to three primary mechanisms with distinct infarct patterns: (1) borderzone infarcts (BZI) due to impaired distal perfusion, (2) territorial infarcts due to distal plaque/thrombus embolization, and (3) plaque progression occluding perforators. The objective of the systematic review is to determine whether BZI secondary to ICAS is associated with a higher risk of recurrent stroke or neurological deterioration.Methods As part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…A post hoc analysis from the SAMMPRIS trial (Stenting Versus Aggressive Medical Therapy for Intracranial Arterial Stenosis) showed that infarct pattern is a strong predictor of recurrent stroke in symptomatic ICAS patients. 9 Among 101 patients, there were more recurrent strokes in the territory with BZI compared with non-BZI patients (14/53 [ 39 The use of perfusion imaging has also been suggested to predict risk of early stroke recurrence in ICAS patients. 40,41 A single-center study evaluated the association between impaired perfusion and early stroke recurrence in patients with symptomatic ICAS.…”
Section: Hypoperfusion-hemodynamic Failurementioning
confidence: 99%
“…A post hoc analysis from the SAMMPRIS trial (Stenting Versus Aggressive Medical Therapy for Intracranial Arterial Stenosis) showed that infarct pattern is a strong predictor of recurrent stroke in symptomatic ICAS patients. 9 Among 101 patients, there were more recurrent strokes in the territory with BZI compared with non-BZI patients (14/53 [ 39 The use of perfusion imaging has also been suggested to predict risk of early stroke recurrence in ICAS patients. 40,41 A single-center study evaluated the association between impaired perfusion and early stroke recurrence in patients with symptomatic ICAS.…”
Section: Hypoperfusion-hemodynamic Failurementioning
confidence: 99%
“…ntracranial atherosclerotic stenosis (ICAS) is emerging as a compelling cause of ischemic stroke and is associated with a poor prognosis. [1][2][3] The stroke mechanisms of symptomatic ICAS include artery-to-artery embolism, hypoperfusion, branch atheromatous disease, and large vessel occlusion, where artery-to-artery embolism is a result of plaque rupture and hypoperfusion is consequent to compromised blood flow, [4][5][6] which often coexist. 4 From a physics standpoint, hemodynamic impairment may have a significant influence on the stroke mechanism of atherosclerotic origin.…”
mentioning
confidence: 99%
“…[1][2][3] The stroke mechanisms of symptomatic ICAS include artery-to-artery embolism, hypoperfusion, branch atheromatous disease, and large vessel occlusion, where artery-to-artery embolism is a result of plaque rupture and hypoperfusion is consequent to compromised blood flow, [4][5][6] which often coexist. 4 From a physics standpoint, hemodynamic impairment may have a significant influence on the stroke mechanism of atherosclerotic origin. [7][8][9] For example, a heightened mechanical burden has the potential to induce deformation and mechanical disruption of plaque, while low perfusion pressure may lead to hypoperfusion.…”
mentioning
confidence: 99%